The analysis of the features of training of the teacher of XXI century in the light of European integration processes - Колупаєва, Тетяна Євстафіївна (ScienceRise: Pedagogical Education, 2016)
The theoretical approaches to the problem of reformation of pedagogical education, requirements of the preparation of teacher of new generation, who must have the high professionalism, European culture and competence of the teacher of XXI century and the role of universities in preparation of pedagogical staff under conditions of entering in united European space of higher education are considered in the article. The main components that the teacher of XXI century must have, professional requirements that allow teacher become a full-value citizen of the Europe of knowledge, to be a competitive specialist in pedagogical branch and realize own creative potential in any European or World state were defined. The article deals with traditional and new requirements to the teachers that must be formed in all links of pedagogical education to guarantee the teachers’ ability to work effectively in European educational space